IMPLIKASI TEORI EMPIRISME DALAM PELAKSANAAN PENDIDIKAN DI SEKOLAH DASAR - Gregorius Weu; Finsensius Mbabho; Maria Finsensia Ansel (Jurnal Pendidikan Dasar Flobamorata, 2023)
Philosophy has a great influence on the progress of world education, especially education in Indonesia. The influence given is in the form of pious thoughts from philosophers to change the face of education. Philosophy is mother from all science. In other words the mother of all knowledge.Empiricism makes a real contribution to the world of education. Where are the thoughts from philosophy empiricism pioneered by John Locke, a philosopher from England with a very famous thought, namely the blank sheet of paper.The concept of the blank sheet of paper means that students are likened to white paper or tabula rasa. The impact of this concept is that students really need what is called education. Education is a conscious and planned effort carried out by adults in order to guide children towards developing their talents and interests as well as their potentials to become complete human beings in carrying out this life. Students are learning subjects who really need attention and affection in the educational process. That is, as an individual, students want to get the various knowledge needed to prepare themselves to start experiencing the process of being trained and guided towards maturity both from the cognitive, affective, and psychomotor aspects. These aspects become the essential foundation for the formation of students' self.